An integrative systematic review of employee silence and voice in healthcare: what are we really measuring? - Lainidi, Olga; Jendeby, Mimmi Kheddache; Montgomery, Anthony; Mouratidis, Christos; Paitaridou, Konstantina; Cook, Clare; Johnson, Judith; Karakasidou, Eirini (Frontiers in Psychiatry, 2023)
The history of inquiries into the failings of medical care have highlighted the critical role of communication and information sharing, meaning that speaking up and employee silence have been extensively researched. However, the accumulated evidence concerning speaking-up interventions in healthcare indicates that they achieve disappointing outcomes because of a professional and organizational culture which is not supportive. Therefore, there is a gap with regard to our understanding of employee voice and silence in healthcare, and the relationship between withholding information and healthcare outcomes (e.g., patient safety, quality of care, worker wellbeing) is complex and differentiated. The following integrative review is aimed at addressing the following questions; (1) How is voice and silence conceptualized and measured in healthcare?; and (2) What is the theoretical background to employee voice and silence?. An integrative systematic literature review of quantitative studies measuring either employee voice or employee silence among healthcare staff published in peer-reviewed journals during 2016-2022 was conducted on the following databases: PubMed, PsycINFO, Scopus, Embase, Cochrane Library, Web of Science, CINAHL and Google Scholar. A narrative synthesis was performed. A review protocol was registered on the PROSPERO register (CRD42022367138). Of the 209 initially identified studies for full-text screening, 76 studies met the inclusion criteria and were selected for the final review (N=122009, 69.3% female). The results indicated the following: (1) concepts and measures are heterogenous; (2) there is no unifying theoretical background, and (3) there is a need for further research regarding the distinction between what drives safety voice versus general employee voice, and how both voice and silence can operate in parallel in healthcare. Limitations discussed include high reliance on self-reported data from cross-sectional studies as well as the majority of participants being nurses and female staff. The reviewed research does not provide sufficient evidence on the links between theory, research and implications for practice, thus limiting how research in the field can better inform practical implications for the healthcare sector. Ultimately, the review highlights a clear need to improve assessment approaches for voice and silence in healthcare, although the best approach to do so cannot yet be established.